Are City Logistics Solutions Sustainable? The Case of Cityporto - Gonzalez-Feliu, Jesus; Morana, Joelle (TeMA - Journal of Land Use, Mobility and Environment, 2010)
Urban logistics is a field that studies the best solutions for urban freight distribution with high environmental objectives. However, most actions are started by public authorities without taking into account the impacts of the new organizational schemas in the existing distribution enterprises’ organization. This paper proposes a case study from Padova, Italy: the city logistics system Cityporto, from which the sustainability of such systems is discussed in a Sustainable Development point of view, for both enterprise and collective dimensions, in order to relate the particularities of city logistics to the corresponding supply chains, i.e. to global logistics.